Comparison of front-end frameworks for web applications development - Kaluža, Marin (Array, 2018)
Modern web applications, due to the functionalities they provide in their user interfaces, have a complex program structure. Manually writing a program code, due to the complexity of the entire application, can result in uneven quality and content of individual application parts. Maintaining such developed applications is more difficult. Because of this, web applications are often developed by using different frameworks. A framework allows structuring, simpler and more uniform program script writing, and thus easier web application maintenance. There are various frameworks that can be used in the development of web applications, for different parts of the application. Those analyzed in this paper are used in the development of front end parts of web applications. According to their design, a web application can be developed as the Multi Page (MPA) or the Single Page (SPA). This paper explains the difference between MPA and SPA web applications. The advantages and disadvantages of MPA are demonstrated in relation to SPA web applications. Required characteristics that the framework should have in order to be optimized for creating MPA and SPA web applications are set. The hypothesis has been tested: There is a framework that is optimized for the development of both MPA and SPA applications. Possibilities, architecture and development techniques of a web application using front end frameworks, as well as the suitability of such frameworks for the development of MPA and SPA web applications have been analysed. Choosing a framework for the hypothesis testing has been performed based on the popularity of available frameworks. The required characteristics have been analyzed on the three most popular frameworks: Angular, Vue.js and React-js. It has been shown that the Vue.js framework is the most optimized framework for the development of both MPA and SPA applications.